A Conceptual Analysis: The Inclusion of Elder-Care Funding in Contemporary Waqf Revival in Nigeria - Yakubu, Abu Bakar; Isbahi, Muhammad Baiqun (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2022)
The urgent need for eldercare funding follows an alarming increase in the population of elderly persons aged 65+ within the last two decades, implying the need for countries to prioritize funding in terms of policy and budget. However, most developing countries like Nigeria are lacking in this regard making the search for optional methods that could ensure funding and provision of functional elderly care more evident. Waqf counts as an avenue for social support especially the waqif of religion and philanthropy. Hence, it is a need for a study of the waqf model. The analysis hinged on the structural functionalist theory as presented by Talcott Parsons, (1951). In the current academic discourse on the need to revive waqf, the central argument of this research agrees that the waqf model needs revival but also an orientation towards addressing the excesses generated by population aging across Muslim countries. From the studies reviewed, it is clear that political practices affect the waqf. In addition, a poor application and execution of funds, mismanagement, misappropriation, corruption, and the poor attitude of the Ulama in reviving the age-long institution among others. The paper concludes that the functional role of the waqf in funding areas of social justice makes the waqf a key institution that can address the challenges of eldercare as posed by the aging of the population across Muslim countries. It recommends eldercare funding in the waqf revival debate in addition to addressing the numerous problems affecting the waqf institution for a successful revival towards addressing contemporary issues in Muslim communities in Nigeria.